Lexical Modulation without Concepts. (13th December 2017) - Allott, Nicholas; Textor, Mark
Abstract: We argue against the dominant view in the literature that concepts (understood as the standing meanings of general terms) are modulated in lexical modulation. We also argue against the alternative view that 'grab bags' of information that don't determine extensions are the starting point for lexical modulation. In response to the problems with these views we outline a new model for lexical modulation that dispenses with the assumption that there is a standing meaning of a general term that is modified in the cases under consideration. In applying general terms we intend to conform with our linguistic ancestors and in doing so we take facts about the referents of these terms for granted. In cases of lexical modulation we become aware of facts we took for granted and we need to change the facts we take for granted in order to see ourselves as continuing in a practice. These changes result in utterances of the general term referring to different properties. In general, concepts are neither the starting point for lexical modulation nor the standing meanings of words.